The Impact of Service Quality on Customer Satisfaction: A Study on Selected Retail Stores in India - Hisam, Mohammed Wamique; Sanyal, Shouvik; Ahmad, Moinuddin (International Review of Management and Marketing, 2016)
Shopping in India has undergone a revolution with the introduction of modern formats, multiple channels and huge shifts in consumer buying behavior. Modern retailing has entered into India as is observed in the form of sprawling shopping centers, multi-storied malls and the huge complexes that offer shopping, entertainment and food all under one roof. Several studies have shown that customer satisfaction in retailing depends to a large extent on the perceived quality of service offered by the retailer. Managing perceived service quality means that the firm has to match the expected service and perceived service to each other so that consumer satisfaction is achieved. This paper aims to understand the importance and impact of service quality on the satisfaction of customers in selected retail stores in 3 Indian cities using SERVQUAL and GAP models. The paper also looks at the various service quality models and tries to assess their relative importance in successfully measuring service quality. Weighted averages and Analysis of Variance is applied in relevant places in order to critically examine the customers’ perception towards service quality which will ultimately contribute information for the growth of performance of the organized retail outlets Keywords: Customer Satisfaction, Quality, Reliance, Service, SERVQUAL JEL Classifications: M30, M31